ANALISIS KEPATUHAN PENGELOLAAN KEUANGAN BLUD DAN TINGKAT KEMANDIRIAN RSUD PURI HUSADA TEMBILAHAN TAHUN 2015-2019 - Andy Slamet; Bambang Supeno (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to analyze the Compliance Analysis of BLUD Financial Management on the Level of Independence of the Puri Husada Tembilahan Regional General Hospital which has been designated as a Regional Public Service Agency (BLUD) since 2012. This study uses a descriptive research method. The type used is time series secondary data which includes aspects of BLUD financial management compliance and the hospital's level of independence during the 2015-2019 period. BLUD financial management compliance is measured by looking at the Hospital Performance Evaluation Report and the level of independence is measured by the hospital independence ratio. The analytical method used in this research is descriptive analysis. The results showed that the compliance of BLUD financial management still did not meet the standards, while the level of independence of the BLUD RSUD Puri Husada Tembilahan had met the expected standards.